Development of P2TB Surveillance Information System on Children in Health Office of Surabaya - Neneng Dwi Septiani; Fariani Syahrul; Daniek Suryaningdiah; Rosita Dwi Yuliandari (Humanistic Network for Science and Technology (HNST), 2018)
-